2018
DOI: 10.1080/2331205x.2018.1534306
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to e-cigarette marketing and product use among Mexican American young adults on the US-Mexico border: A pilot study

Abstract: Historically, the tobacco industry has marketed directly to minority groups, which is associated with increased product use; the advent of e-cigarettes poses a new risk. The purpose of this study is to examine associations between exposure to tobacco marketing via traditional and digital marketing channels and ever use of e-cigarettes among Mexican-American young adults. Ninety-two Mexican-American young adults between 18 and 29 years of age (61% female) were recruited from the Cameron County Hispanic Cohort, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…Most respondents who were students in Malaysia received information about e-cigarettes from other students (57.5%), friends (37.5%), and the internet (36.6%) (Puteh et al, 2018). Further research revealed that the probability of ever using e-cigarettes increased by 2.86 (95% CI: 1.11-7.38) for each source of communication for respondents who were exposed to digital pro-e-cigarette messages through the internet or Facebook (Herrera et al, 2018). According to research by Istiqomah et al (2016), most respondents received support from the reference group because they were offered at least one electronic cigarette from friends.…”
Section: Discussionmentioning
confidence: 97%
“…Most respondents who were students in Malaysia received information about e-cigarettes from other students (57.5%), friends (37.5%), and the internet (36.6%) (Puteh et al, 2018). Further research revealed that the probability of ever using e-cigarettes increased by 2.86 (95% CI: 1.11-7.38) for each source of communication for respondents who were exposed to digital pro-e-cigarette messages through the internet or Facebook (Herrera et al, 2018). According to research by Istiqomah et al (2016), most respondents received support from the reference group because they were offered at least one electronic cigarette from friends.…”
Section: Discussionmentioning
confidence: 97%
“…Digital media is a core part of the e-cigarette industry's strategy to promote products and its industry ( 13 , 14 ). Social media, in particular, allows for products to be marketed to young people across borders at low cost and under less oversight than traditional media platforms.…”
Section: Introductionmentioning
confidence: 99%